Pendampingan Masyarakat Pengrajin Rotan dalam Pengelolaan Limbah Ramah Lingkungan melalui Edukasi Eco-Design di Desa Kueh - Aceh Besar - Sentia, Prima Denny; Asmadi, Didi; Ilyas, Ilyas; Riza, Medyan; Sari, Cut Maya Aprita; Hidayaturrahmi, Hidayaturrahmi (Nawadeepa: Jurnal Pengabdian Masyarakat, 2025)
Kueh Village, located in Aceh Besar District, is one of the centers of rattan handicrafts. However, the rattan production process in this village generates unmanaged solid and liquid waste, resulting in environmental pollution. This community service program aims to improve artisans' awareness and skills in waste management through the application of the Eco-Design concept. The implementation methods included socialization, training on waste processing, and the provision of supporting production equipment. The results showed that artisans successfully processed solid waste into new value-added products such as souvenirs, while liquid waste was minimized through safe storage and environmentally friendly dye alternatives. This program demonstrated a positive impact on artisan knowledge, environmental sustainability, and local economic enhancement.